PERENCANAAN SKEMA SISTEM INFORMASI UNTUK AKTIVITAS MANAJEMEN - Pradana, Mahir (Ekombis Review, 2016)
Mahir Pradana; The search for as much information as possible is needed to achieve maximum results in a management process. Information is also needed as a source of evaluation of the development of an organization, institutions, companies, and departments. Thus, the management process is inseparable from the use of information systems, which is a set of components that are interconnected, collect, process the store, and distribute information to support decision-making and control in an organization. This article examines the theories of management information system to be used as a reference in the domain of management information systems.Keywords: Management Information Systems, Use Of Information Systems, The Value Of Information Technology.